Regulation of T helper cell responses during antigen presentation by norepinephrine‐exposed endothelial cells. Issue 1 (20th December 2017) - Xu, Linghui; Ding, Wanhong; Stohl, Lori L.; Zhou, Xi K.; Azizi, Shayan; Chuang, Ethan; Lam, Jimmy; Wagner, John A.; Granstein, Richard D.
Summary: Dermal blood vessels and regional lymph nodes are innervated by sympathetic nerves and, under stress, sympathetic nerves release norepinephrine (NE). Exposure of primary murine dermal microvascular endothelial cells (pDMECs) to NE followed by co‐culture with Langerhans cells (LCs), responsive CD4 + T‐cells and antigen resulted in modulation of CD4 + T‐cell responses. NE‐treatment of pDMECs induced increased production of interleukin (IL)‐6 and IL‐17A while down‐regulating interferon (IFN)‐ γ and IL‐22 release. This effect did not require contact between pDMECs and LCs or T‐cells and depended upon pDMEC production of IL‐6. The presence of NE‐treated pDMECs increased the proportion of CD4 + T‐cells expressing intracellular IL‐17A and increased IL‐17A mRNA while decreasing the proportion of IFN‐ γ ‐ or IL‐22‐expressing CD4 + T‐cells and mRNA levels for those cytokines. Retinoic acid receptor‐related orphan receptor gamma (ROR‐ γ t) mRNA was significantly increased in CD4 + T‐cells while T‐box transcription factor (T‐bet) mRNA was decreased. Intradermal administration of NE prior to hapten immunization at the injection site produced a similar bias in draining lymph node CD4 + T‐cells towards IL‐17A and away from IFN‐ γ and IL‐22 production. Under stress, release of NE may have significant regulatory effects on the outcome of antigen presentation through actions on ECs with enhancement of inflammatory skin disorders involving IL‐17/T helper type 17 (Th17) cells. Abstract : Exposure of microvascular endothelial cells (ECs) to the stress hormone and sympathetic nerve transmitter norepinephrine endows ECs with the capacity to bias the outcome of antigen presentation to responsive T‐cells, acting as bystanders, away from the Th1 pole and towards the Th17 pole. This effect does not require cell–cell contact and might explain, in part, stress‐induced exacerbation of disorders involving Th17/IL‐17A immune responses.